Chlorophyll performances as an indicator of compost quality: Effectiveness of liquid humic substances and compost tea - Bouchra El Hayany; Khaoula En-Nejmy; Ghizlen El Mezouari El Glaoui; Mohamed Hafidi; Loubna El Fels (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This study was carried out with the aim of improving the use of compost products as compost tea and humic substances fertilizers, to study the evolution and the degree of compost maturity, and to use the chlorophyll as an indicator of compost quality.Method: The compost tea and humic substances were prepared from different stages of a windrow compost (1/2 dewatered lagooning sludge + 1/2 green waste), the mineral content was investigated using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) analysis. The growth test was carried out in a greenhouse for two months on two plants: Trigonella foenum-graecum (Fenugreek) and Lepidium sativum (Cress). Plant observations including stem elongation, biomass, stomatal conductance, chlorophyll fluorescence and total chlorophyll content in the leaf were investigated at the end of the experiment.Results: The findings revealed that compost tea and humic substances resulting from the initial stage and intermediate stage of composting present a lower stimulating effect on plants growth (biomass: 0.83-1.42 g/plant; total chlorophyll: 0.48-0.71 mg/plant). While those from the final stage showed significant effects on biometric and physiological properties (biomass: 1.399-2.396 g/plant; total chlorophyll: 0.74-0.83 mg/g).  Furthermore, the chlorophyll performance, as a good indicator to determine plant stress and soil pollution, confirmed the maturity and the good quality of the final compost.Conclusion: Compost tea and humic substances treatments approved their bioactive properties and beneficial effects on plant growth and their physiological properties.